PENGARUH KEPEMIMPINANTERHADAP KOMITMEN DAN KINERJA GURU MADRASAH TSANAWIYAH PADAPONDOK PESANTREN DI KOTA MATARAM - Muhammad Birruni (JMM UNRAM - MASTER OF MANAGEMENT JOURNAL, 2015)
This study aims to reveal the influence of leadership on organization commitment and theperformance of Islamic Junior High School (MTs) teachers in boarding school in Mataram city. Thestudy populations consisted of 358 fully-employed teachers who worked in Islamic Junior HighSchools of Pondok Pesantren (Boarding Schools) in Mataram City. By using Slovin formula, theresearcher took 79 teachers as the study samples. The study employed a research instrument in theform of a questionnaire containing question related to the variables under investigation, i.e.leadership, organizational commitment and teacher performance. The data were analyzed by usingSPSS path analysis. The result of this study reported that there was positive and significant impactof leadership on organizational commitment and the Performance of the Islamic Junior High Schooltechers at the Pondok Pesantren being investigated in Mataram city. Result of the study suggest thatto improve the performance of the Islamic Junior High School teachers, school leaders are adviced tokeep exercising their leadership skills and commitment to her organization.Kata Kunci: Kepemimpinan, Komitmen Organisasi, Kinerja, dan Analisis Jalur.